On Presumptions, Burdens of Proof, and Explanations - Bodlović, Petar (Informal Logic, 2020)
On the standard view, all presumptions share the same deontic function: they asymmetrically allocate the burden of proof. But what, exactly, does this function amount to? Once presumptions are rejected, do they place the burden of arguing, the burden of explanation, or the most general burden of reasoning on their opponents? In this paper, I take into account the differences between cognitive and practical presumptions and argue that the standard accounts of deontic function are at least ambiguous (because two types of presumptions entail distinct conceptions of the “burden of proof”), and likely implausible. As a result, they require qualifications.